TH6.8 The Utility and Impact of Advanced Nurse Practitioners in Unplanned Surgical Admissions: A Review of the Literature. (9th August 2022) - Riley, Anna; Tod, Angela; King, Rachel; Chan, Anthony; Robertson, Steve
Abstract: Aims: Advanced Nurse Practitioners (ANP) are well established within acute medical and Critical Care environments. The evolution of surgical ANPs have tended towards preoperative roles, such as anaesthesia or scrub, with few clinical roles involving the assessment of acute patients or inpatient care. The Royal College of Surgeons of England have recently recognised, by professional membership, the roles of non-medical members of the surgical team, such as ANPs and physician associates. This review explores the areas of impact of ANPs on the emergency General Surgery service provision to help develop the role of the modern surgical ANP. Methods: A scoping literature review was performed to identify themes of ANP function and outcome. Search terms such as "Advanced Nurse Practitioners", "Surgical Assessment Units" and "outcomes" were combined with Boolean operators to query PubMed, BNI, CINAHL, Google Scholar and HMIC databases. Studies in the last decade were included. Results: We identified and screened 54 unique articles. 40 articles were reviewed for eligibility and 21 were included in this review. A thematic analysis identified the impact of ANPs on the process of care (such as assessment and treatment waiting times and patient satisfaction) and outcomes of care (readmission rates, length of stay and cost-effectiveness). Conclusion: Research into the impact of ANPs are largely focused on objective outcome measures and within non-surgical specialties. Whilst this review demonstrates the positive aspects of ANP care on emergency care, we identify a paucity of evidence on patient-focused outcomes and the impact of ANPs on the patient journey within surgery.